Tracks of change - Prasad, Ritika, 1975- (New Delhi, India)
x, 315 sayfa
Keywords: “Discusses how railway technology, travel, and infrastructure became increasingly and inextricably woven with everyday life in colonial South Asia, how people negotiated this increasing presence of railways in their lives, and how the ensuing processes has materially shaped South Asia's present“ --